Geospatial Function in Tsunami Disaster Mitigation - Olivia Oktorie (Pascasarjana, Universitas Negeri Padang, 2020)
Geospatial data is generated from a combination of Mapping Science, Remote Sensing and Geography Information System (GIS). Scientifically, GIS is the key in strengthening the geospatial function in determining a location, pathways, and zones of an area, both for preparing disaster mitigation maps, disaster prone zones, and community evacuation locations. GIS has the ability to connect various data at a certain point on the earth, combine them, analyze and finally map the results.